22.2% Efficiency n-type PERT Solar Cell. (August 2016) - Cai, Wenhao; Yuan, Shengzhao; Sheng, Yun; Duan, Weiyuan; Wang, Zigang; Chen, Yifeng; Yang, Yang; Altermatt, Pietro. P.; Verlinden, Pierre J.; Feng, Zhiqiang
Abstract: N-type PERT (passivated emitter rear totally diffused) silicon solar cells promise high and stabilized conversion efficiencies. As relative big contact recombination and shading losses were introduced by traditional front screen-printed metallization, we applied Ni/Cu/Ag plating to form the front metallization grid, and we also applied PVD (physical vapor deposited) aluminum for the rear side contacts for better optical reflection. With help of laser ablation, the front and rear metallization fraction can be reduced to less than 1%, which benefits both V oc and J sc . In order to increase J sc further, we optimized the front AR coating and the back reflection. Based on these technologies, we reach efficiencies of up to 22.2% on 5 inch, commercial grade Cz n- type wafers. For further improvement, we reproduce the cell performance by simulation with Sentaurus to do a power loss analysis to quantify recombination and resistive losses. These simulations indicate that emitter recombination and the internal resistance are the top two power loss sources for our 22% PERT cells.